An Improved Thermoeconomic Diagnosis Method: Applying to Marine Diesel Engines - Nan Xu; Longbin Yang; Yu Guo; Lei Chang; Guogang Zhang; Jundong Zhang (Journal of Marine Science and Engineering)
Thermoeconomic diagnosis methods are designed to identify faulty components and evaluate the economic implications of these faults. However, these diagnostic techniques often struggle to filter out interference from induced factors during the diagnosis process. When multiple components malfunction simultaneously, these methods may fail to effectively identify all the faulty components. To address these challenges, this article introduces an improved thermoeconomic diagnosis method that integrates the traditional diagnosis method with the operational characteristic curves of the components. This improved method facilitates a more precise differentiation between the impacts of faults on each component, categorizing them into intrinsic and induced parts. The intrinsic part arises from the component’s inherent failure, while the induced part results from interactions among different components or adjustments made by the control system. The improved method generates fault diagnosis indicators and economic assessment indicators based on this classification, allowing for the identification of faulty components and the evaluation of the economic consequences of these faults. The proposed method was tested on a MAN 6S50 MC-C8 diesel engine and validated under two real operating conditions, where multiple faults were intentionally introduced in various components. The results demonstrated that the new method accurately identified all faulty components within the marine diesel engine and assessed the economic impacts of these faults.